Polyvinyl alcohol/chitosan composite films with pomegranate peel powder: Improved bioactivity and biodegradability - Isman, Nese; Sicak, Yusuf; Terzioglu, Pinar (Elsevier, 2025)
The fact that petroleum-derived plastic packaging has a very short lifespan that causes serious environmental problems. The interest in development of biocomposite films with suitable biodegradability is increasing day by day. In the present study, polyvinyl alcohol/chitosan (PVA/CS) bioactive composite films containing pomegranate peel powder (PPP) were developed by casting method. The PVA/CS films with PPP (1-3 % w/w) were investigated to determine the physical, mechanical, structural, barrier, soil biodegradability and antioxidant properties. Surface morphology was observed by SEM and peel powder integration to the structure was revealed clearly. It was observed that the tensile strength of PPP incorporated films (22.76 +/- 0.89-19.63 +/- 0.98 MPa) were lower than the neat film (35.03 +/- 2.67 MPa), whereas the elongation at break values of biofiller added films were higher. Additionally, the water contact angle values of the films ranged from 105.2 degrees +/- 0.56-83.1 degrees +/- 0.72, showing a decreasing trend with increasing pomegranate peel powder concentration. While the water vapor permeability of the films increased with higher pomegranate peel powder content, the water solubility values initially decreased. The alteration in color of films was detected with incorporation of pomegranate peel powder. Moreover, antioxidant activity reached its highest value (IC50:6.60 +/- 0.42 and 7.17 +/- 0.34 mu g/mL for DPPH and ABTS, respectively) with 3 % w/w PPP addition. According to soil burial test results, the 2 % w/w PPP incorporated films showed the highest biodegradability (similar to 67 %).
Keywords: Biofiller; Pomegranate peel powder; Soil biodegradability; Sustainable biocomposite